Antagonistic effect of a Trichoderma sp. Strain over Fusarium sp In a tomato plant Rio Grande (Solanum lycopersicum - Manayay Guevara, Claudia Ana Luz (2016)
Fusarium is one ofthe main illnesses that affect the tomato crop (Lycopersicon lycopersicum) being this illness caused by several species of genre Fusarium como Fusarium oxysporum f. sp. Lycopersici, Fusarium oxysporum f. sp. radicis-lycopersici, y Fusarium solani. In this research the antagonistic effect of a Trichoderma sp. strain was evaluated, over Fusarium sp., in tomato plants cultivated in greenhouse; besides compare the biocontrol action of the Trichoderma sp strain with an alternative of control chemistry given for the fungicide Benomyl and with a commercial formulation of Trichoderma viride. The commercial strain of Trichoderma viride demonstrated a high protectress efficiency, with 90% of plants survival, which was always top to Trichoderma sp strain that reached 70% of survival. The benomyl fungicide offered a wide protection of tomate plants at fungus attack Fusarium sp being bigger exercised by the strain Trichoderma viride. When the bío controls were mixed with the benomyl fungicide, the fungicide produced a detrimental effect in the action as of the strain Trichoderma sp as strain commercial formulation Trichoderma viride; being stronger in this last mentioned.